Rewire your anxious brain for teens ebook Using cbt, neuroscience, and mindfulness to help you end anxiety, panic, and worry. - Kissen, Debra (Instant Help Solutions., 2020)
It's time to retrain your brain! In this go-to guide for teens, four anxiety experts offer tangible tips and tools you can use every day to rewire your anxious brain; manage fears, stress, and worry; and get back to living your life. When you're feeling anxious, it can seem like the whole world is crashing in around you. Your heart starts racing, your thoughts feel jumbled, and you may feel like something terrible is going to happen, or worse. You aren't alone. In fact, millions of teens experience anxiety. The good news is that there are proven-effective tools you can use now to take control of your anxiety so you can focus on the stuff you love. This book will guide the way. Drawing on powerful cognitive behavioral therapy (CBT), neuroscience, mindfulness, and acceptance commitment therapy (ACT), this book will show you the ten most effective methods for "rewiring" your anxious brain. You'll learn: How to calmly observe your anxiety What feeds your anxiety, and how you can "starve" it instead Guided meditations for overcoming anxious thoughts Strategies to help you balance your emotions when fears and worries show up How to deal with uncertainty, perfectionism, and procrastination Most importantly, you'll learn that you are stronger than your anxiety, and you have the power to take control of your fears. Let's face it—being a teen today is stressful and sometimes scary. But if you're ready to put anxiety in its place and start focusing on the things that matter to you the most, this much-needed guide can help get you started.